Mutational spectrum of BRCA genes in Egyptian patients with breast cancer - Wafaa Elmetnawy; Heba Nader; Tamer ElNahas; Salwa Sabet; Heba Bassiony; Yasser ElNahass (Scientific Reports)
Abstract The rising incidence of breast cancer (BC) among Egyptian females with a mortality rate of 11% and younger age at diagnosis implied the study of the interplay of BRCA gene variants with other BC risk factors. The study enrolled 500 BC Egyptian females with a mean age of 47.29 ± 13.26 years for whom BRCA1/2 testing was offered. A history of BC and/or other related cancer was recorded for all patients. Peripheral blood samples were obtained for genomic DNA extraction in view of germline BRCA gene testing on the MiSeq platform. A positive family history was reported in 352 patients (70.4%). Patients with hormone receptor–positive (HR+) BC constituted 195 cases (39%) cases, while 305 patients (61%) had hormone receptor–negative (HR−) BC. Among the HR− group, 268 patients (53%) had triple-negative BC (TNBC), and 37 patients had low estrogen receptor (ER) (1–10%) and/ or low progesterone receptor (PR) expression with HER2 negative status. Patients with HER2-positive BC were excluded from the enrollment and directed to specific targeted therapy. Variants were classified according to the American College of Medical Genetics (ACMG) and the Association for Molecular Pathology (AMP) criteria. Carriers of gBRCA1/2 PVs/LPVs were 58 patients (11.6%) of whom 34 (6.8%) had BRCA1 PVs/LPVs and 24 (4.8%) had BRCA2 PVs/LPVs. Patients with TNBC demonstrated a higher rate of gBRCA1/2 PVs/LPVs (17.5%). We recorded 55 PVs/LPVs in both genes, 44 single nucleotide variants (SNVs), and 11 copy number variations (CNVs). Three novel gBRCA1 LPVs; c.2791del, c.361G>T and c.4431dup and two novel gBRCA2 LPVs; gBRCA2 c.3139del and c.5690 dup were identified. Variants of uncertain significance (VUS) were found in 22 patients, of whom 13 (59%) had a positive family history of breast/ovarian cancer. Genomic testing for BRCA1/2 status as part of a routine BC diagnostic workup contributes to comprehensive BC risk assessment. Trial registration: Egyptian National Cancer Institute IRB approval number: 2301-305-051. Date of registration: 24th Jan 2023.